Preoperative excessive lateral anterior tibial subluxation is related to posterior tibial tunnel insertion with worse sagittal alignment after anterior cruciate ligament reconstructions - Liu, An; Ye, Xiaojun; Li, Congsun; Yang, Weinan; Yan, Shigui; Xin, Zengfeng; Wu, Haobo (Frontiers in Surgery, 2022)
Objective To investigate whether preoperative lateral anterior tibial subluxation (LATS) measured from magnetic resonance imaging (MRI) can influence tibial insertion and postoperative sagittal alignment after anterior cruciate ligament reconstructions (ACLRs). Methods 84 patients who underwent single-bundle ACLRs were retrospectively investigated. Among them, 39 patients (LATS of <6 mm) 23 patients (LATS of ≥6 mm and <10 mm) and 22 patients (excessive LATS of ≥10 mm) were defined as group 1, 2 and 3, respectively. LATS, the position of graft insertion into tibia as ratio of anterior-posterior width (AP ratio) and the sagittal graft angle (SGA) were postoperatively assessed from MRI at 2-year follow-up. Following linear regression analyses were employed. Results The group 3 exhibited the largest preoperative LATS and remained the most postoperative LATS. Moreover, the group 3 possessed the most posteriorly located tunnel insertion with the largest AP ratio and the most vertical graft orientation. Of all included patients, a moderate correlation was demonstrated between pre- and postoperative LATS (r = 0.635). A low correlation was observed between preoperative LATS and AP ratio (r = 0.300) and a moderate correlation was displayed between AP ratio and SGA (r = 0.656). Conclusion For ACL injuries with excessive LATS (≥10 mm), most posteriorly located tibial insertion was found out, and worse sagittal alignment containing high residual LATS was associated with more vertical graft orientation following ACLRs.